Comparative Study on the Reservoir Characteristics and Development Technologies of Two Typical Karst Weathering-Crust Carbonate Gas Reservoirs in China - Haijun Yan; Ailin Jia; Fankun Meng; Qinyu Xia; Wei Xu; Qingfu Feng; Wenjun Luo; Xinyu Li; Xun Zhu; Yicheng Liu (Geofluids)
Carbonate reservoirs are the main reservoir types in China, which occupy the large ratio of reserves and production at present. The high-efficiency development of carbonate reservoirs is of great significance to assure the stability of national energy supply. The Lower Paleozoic reservoir in Jingbian gas field and the Sinian reservoir in Anyue gas field are two typical carbonate gas reservoirs, and their successful development experiences can provide significant references for other similar carbonate gas reservoirs. For Jingbian gas field, it is a lithological-stratigraphic reservoir developed in a westward monocline and multiple rows of nose-fold structures, and is a stable craton basin with simple palaeognomy distribution and stable connectivity, which has complex gas-water distribution. However, for Anyue gas field, it is a lithological-structural reservoir with multiple tectonic high points and multiple fault systems, and is biological dune beach facies under extensional setting with highly differentiated inside of the block in palaeognomy characteristics, which has limited connectivity and tectonic side water is in a local area. The difference of gas reservoir characteristics leads to the diverse development strategies. For these two gas reservoirs, although there are some similar aspects, such as the screen of enrichment areas, the application of irregular well pattern and reservoir stimulation techniques, the criteria of enrichment areas, the well types, and the means of reservoir stimulation are absolutely different. In addition, due to the differences of control reserves and production capacity for these two kinds of reservoirs, the mode of stable production is also different. The effective development of Jingbian gas field can give some references to the future exploitation on the Sinian gas reservoir. Firstly, the sedimentary characteristics should be studied comprehensively. Secondly, the distribution pattern and distribution characteristics of the palaeognomy should be found and determined. Thirdly, the distribution of fracture system in the reservoir should be depicted finely. Finally, dynamic monitoring on the production performance should be strengthened, and the management for this gas field should be improved further. The findings of this study can help for better understanding of the Karst weathering-crust carbonate gas reservoir formation characteristics and the optimal development technologies that should be taken in practice.